Activation of peroxydisulfate by carbon nanotube for the degradation of 2, 4-dichlorophenol: Contributions of surface-bound radicals and direct electron transfer. (November 2021) - Chen, Chien-Yu; Cho, Yi-Chin; Lin, Yi-Pin
Abstract: Carbon materials have been used to activate peroxydisulfate (PDS) for the degradation of organic pollutants. The mechanism involved, especially whether radicals are formed in these processes, is still under debate. In this research, multi-walled carbon nanotube (MWCNT) was employed to activate PDS for the removal of 2, 4-dichlorophenol (2, 4-DCP). The effects of solution pH, PDS concentration, 2, 4-DCP concentration, and MWCNT loading on the degradation of 2, 4-DCP were investigated. The mechanism was explored via radical scavenging experiments, electron paramagnetic resonance (EPR) and MWCNT surface characterization. The results showed that the rate of 2, 4-DCP degradation increased with the increasing solution pH, PDS concentration and MWCNT loading. The presence of OH and SO4 − signals in EPR studies, no inhibitory effect in radical scavenging experiments, and the chlorination of MWCNT observed by X-ray photoelectron spectroscopy (XPS) suggested that surface reactions involving both surface-bound radicals and direct electron transfer were responsible for 2, 4-DCP degradation. Reusability tests showed that the surface sites responsible for surface-bound radical formation were poisoned after PDS activation, while those responsible for direct electron transfer remained active after five cycles. This research provided the first in-depth insights for the dual roles of MWCNT in the PDS activation process. Graphical abstract: Image 1 Highlights: MWCNT effectively activated PDS to degrade 2, 4-DCP. Influences of PDS concentration, MWCNT loading and pH were investigated. Surface-bound radicals and direct electron transfer were important. Activation site for surface-bound radical formation was poisoned. Direct electron transfer persisted after several cycles of operation.